2023
DOI: 10.1123/jsr.2021-0336
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Knee Extension Strength at 3 and 6 Months After Anterior Cruciate Ligament Reconstruction

Abstract: Context: Deficits in knee extension strength after anterior cruciate ligament reconstruction have been a major problem. The inadequate recovery of the knee extension strength of surgical limb reportedly delays return to sports and increases reinjury risk. Accordingly, the early detection of knee extension strength deficits after reconstruction may help plan early interventions to manage impairment. This study aimed to clarify the association between knee extension strength at 3 and 6 months after anterior cruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…The results also showed that knee extensor strength at 6 months postoperatively was associated with the results at 3 months postoperatively, supporting the findings from a previous study [20]. The LSI cut‐off value of 72.0% at 3 months postoperatively was a clear indicator for the patients to return to their sporting activities after 6 months postoperatively.…”
Section: Discussionsupporting
confidence: 88%
“…The results also showed that knee extensor strength at 6 months postoperatively was associated with the results at 3 months postoperatively, supporting the findings from a previous study [20]. The LSI cut‐off value of 72.0% at 3 months postoperatively was a clear indicator for the patients to return to their sporting activities after 6 months postoperatively.…”
Section: Discussionsupporting
confidence: 88%
“…Although their study population was similar in age (16.1 ± 1.4 years) and gender distribution (54% female), a bone-patellar tendon-bone autograft was used and return to sport testing occurred later (7.3 ± 1.3 months). Additionally, Mitomo et al 18 examined the three-and six-month limb symmetry index of isokinetic quadriceps peak torque in young adults following primary ACLR with hamstring autograft. Despite the current study's examination of normalized quadriceps peak torque, threemonth isokinetic quadriceps limb symmetry index accounted for a similar level of variance (34.9%) in limb symmetry index at six months, comaparitively.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the current study's examination of normalized quadriceps peak torque, threemonth isokinetic quadriceps limb symmetry index accounted for a similar level of variance (34.9%) in limb symmetry index at six months, comaparitively. 18 While limb symmetry indices are commonly used to establish desired performance thresholds after ACLR, the uninvolved limb may experience deterioration in function leading to an overestimation of strength and function for the injured limb. [28][29][30] It has also been reported that isometric quadriceps strength, when normalized to body mass, was a better predictor of high self-reported function (subjective International Knee Documentation Committee index ≥ 90%) after ACLR when compared to the quadriceps strength limb symmetry index.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation